2013
DOI: 10.1002/ppap.201300015
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of the Polyimide Films by Electrical Discharges in Water

Abstract: Pulsed electrical discharges in distilled water were used for the surface modifications of the aromatic polyimides. Optical emission spectroscopy has shown the formation of excited species in the plasma due to water dissociation and ionization. The reactive species have induced surface modifications of the polymer films which were investigated by FTIR, AFM, XPS, and static contact angle measurements. The surface hydrophobicity of the polyimide films increased with the plasma treatment time due to the segregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Samples of 6FDA‐MMDA PI films that were previously treated by discharges generated in water with microsecond high voltage pulses have shown that the CO band of the imide group shifted gradually to lower wavenumbers (from 1 730 cm −1 for a 2 min plasma treatment and to 1 670 cm −1 for a treatment of 6 min) . This blue shift is associated with attractive electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of 6FDA‐MMDA PI films that were previously treated by discharges generated in water with microsecond high voltage pulses have shown that the CO band of the imide group shifted gradually to lower wavenumbers (from 1 730 cm −1 for a 2 min plasma treatment and to 1 670 cm −1 for a treatment of 6 min) . This blue shift is associated with attractive electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorine‐containing polyimides treated by N 2 plasma have shown a significant defluorination of the surface and an increase of water absorption . More recently it was observed that treatment of fluorine‐containing polyamides by plasma that is generated in water resulted in an increase in surface hydrophobicity . The content of the functional groups containing oxygen (such as hydroxyl) on polypropylene films treated by plasma in liquids was found to exceed a similar functionalization that was achieved by oxygen glow discharge plasmas by a factor of two (up to ca.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of salts had a small effect (only a difference of about 10°), and the absence of cobalt chloride resulted in a gradual increase in contact angle. 14) Moreover, the presence of cobalt chloride in the PI films resulted in an increase in contact angle after 10 min of nanosecond treatment, and by increasing the plasma treatment time, the contact angle slightly decreased to 78°.…”
Section: Contact Angle Measurementsmentioning
confidence: 99%
“…[10][11][12] On the other hand, fluorinated PIs have attracted much attention owing to the decrease in the degree of CT interaction caused by CF 3 -substituted diamines. [12][13][14] The introduction of hexafluoropropanedianhydride (6FDA) to the polyimide main chain derived from dianhydrides weakens the intermolecular CT owing to the bulky substituent group -C(CF 3 ) 2 -, which prevents the molecular packing of polyimide films. 14) In the case of cobalt-modified PIs, note that cobalt(II) chloride groups may also diffuse preferentially through amorphous regions, forming charge transfer complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation